Application of engineered yeast strain fermentation for oligogalacturonides production from pectin-rich waste biomass. (March 2020) - Yang, Guojun; Tan, Haidong; Li, Shuguang; Zhang, Meng; Che, Jia; Li, Kuikui; Chen, Wei; Yin, Heng
Graphical abstract: Highlights: First production of oligogalacturonides (OGs) directly from citrus peel wastes. An innovative green and novel fermentation strategy has been developed. After fermentation for 72 h, the DP of OGs was ranging from 2 to 7. Abstract: Citrus wastes disposal is a problem faced by many juice plants due to high disposal costs. However, the citrus peel wastes (CPW) biomass, as bulk bioresources from the agro-industrial waste, is a good source of pectin. Present study aimed to utilize these CPW biomass by engineered yeast strain fermentation with an inexpensive method to produce oligogalacturonides (OGs). The results showed that the engineered yeast strain fermentation can produce significant amounts of OGs with the degree of polymerization ranged from 2 to 7 from the CPW bioresources. Under the optimized conditions using the response surface methodology, the best OGs yield were 26.1%. The present work is the first to use the engineered yeast strain for direct CPW biomass fermentation produced the OGs. We thereby paved a new way to utilize the pectin-rich bioresources.